Projeto estrutural de molas helicoidais de compressão utilizando o programa Microsoft Excel - Sousa, Nathan Major de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The purpose of the work is to design a compression spring that will work on fatigue and its main purpose is to serve as a support material for undergraduates. The project will use the Excel \ VBA programming language, where after inserting some input data the user will receive important data from approved springs such as weight, fatigue safety coefficient and main geometric factors, as well as graphs for better understanding and analysis. The program respects some limitations imposed by the technical literature and the user will be warned when to make some mistake, guaranteeing the fidelity of the results. Often more than one spring will be approved, then suggestions will be given for the choice of the ideal spring, however the user should be aware of the needs of your project. Because it is similar to the exercises done in the classroom and use a tool already known to the students, the material is of great interest to them. As a secondary objective the program can be improved for use by spring manufacturers and vendors

A finalidade do trabalho é fazer o projeto de uma mola de compressão que trabalhará sobre fadiga e tem como objetivo principal servir como material de apoio aos alunos de graduação. O projeto fará uso da linguagem de programação Excel\VBA, onde após o usuário inserir alguns dados de entradas ele receberá dados importantes das molas aprovadas como peso, coeficiente de segurança para fadiga e principais fatores geométricos, além de gráficos para melhor compreensão e análise. O programa respeita algumas limitações impostas pela literatura técnica e o usuário será advertido quando cometer algum equívoco, garantindo assim a fidelidade dos resultados. Muitas das vezes mais de uma mola será aprovada, então sugestões serão dadas para a escolha da mola ideal, porém o usuário deve estar atento as necessidades do seu projeto. Por ser similar aos exercícios feito em sala de aula e usar uma ferramenta já conhecida dos alunos, o material se mostra de grande interesse para os mesmos. Como objetivo secundário o programa pode ser melhorado para uso de fabricantes e vendedores de mola
Structural design of helical compression springs using the program Microsoft Excel
Keywords: Molas (Mecanismo); Máquinas; Excel for Windows (Programa de computador); Springs (Mechanism)